A produção de Habitação Social em Indaiatuba/SP - Santos, Ingrid Rosa dos (Universidade Federal de São Carlos, 2022)
This work aims to analyze, in Indaiatuba, a medium-sized city in the interior of the State of São Paulo, the relationship between the implementation of projects dedicated to social housing, from the first projects in the 1970's to the most recent, produced by the Program Minha Casa Minha Vida until 2020, and the consequences arising from these projects in the urban environment. It seeks to assess the role that legislation – federal and municipal – played in these cases, and how urban fragmentation impacted the formation and configuration of these spaces.
Production of Social Housing in Indaiatuba/SP
Keywords: Habitação Social; PMCMV; Espaço Urbano; Indaiatuba; Social Housing; Urban Space; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA